2021
DOI: 10.3892/etm.2021.10605
|View full text |Cite
|
Sign up to set email alerts
|

Osthole suppresses the proliferation and induces apoptosis via inhibiting the PI3K/AKT signaling pathway of endometrial cancer JEC cells

Abstract: Osthole, a natural product extracted mainly from fruits of Fructus Cnidii, possesses multiple pharmacological functions, including anti-inflammatory, anti-convulsant and anticancer effects. However, the effects of osthole in endometrial cancer (EC) is not fully understood. In the present study, EC cell lines, including JEC, KLE and Ishikawa cells and normal human cervical epithelial cells (HcerEpic) were applied to detect the anticancer effect of osthole. The present study demonstrated that osthole inhibited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In recent years, the incidence of endometrial cancer has been increasing (Crosbie et al, 2022). Osthole (200 µM) was found to inhibit cellular proliferation and induce apoptosis in an Frontiers in Pharmacology frontiersin.org endometrial cancer cell line (JEC) by inhibiting the PI3K/AKT signaling pathway, and these findings were confirmed in an in vivo study of cancer cell growth in a nude mouse xenograft model (Liang et al, 2021). In another study, an increasing dose of osthole (50, 100, 200 μM) inhibited cellular proliferation and induced apoptosis in endometrial cancer cell lines (Ishikawa, KLE) by upregulation of miR-424 and downregulation of its target gene cytoplasmic polyadenylation element-binding protein 2 (Lu et al, 2020).…”
Section: Reproductive Systemmentioning
confidence: 87%
“…In recent years, the incidence of endometrial cancer has been increasing (Crosbie et al, 2022). Osthole (200 µM) was found to inhibit cellular proliferation and induce apoptosis in an Frontiers in Pharmacology frontiersin.org endometrial cancer cell line (JEC) by inhibiting the PI3K/AKT signaling pathway, and these findings were confirmed in an in vivo study of cancer cell growth in a nude mouse xenograft model (Liang et al, 2021). In another study, an increasing dose of osthole (50, 100, 200 μM) inhibited cellular proliferation and induced apoptosis in endometrial cancer cell lines (Ishikawa, KLE) by upregulation of miR-424 and downregulation of its target gene cytoplasmic polyadenylation element-binding protein 2 (Lu et al, 2020).…”
Section: Reproductive Systemmentioning
confidence: 87%
“…and various other plants belonging to the Apiaceae family (Sun et al, 2021). An increasing number of studies have demonstrated that osthole has anticancer effects on a variety of cancers (Shokoohinia et al, 2018), including glioma (Huangfu et al, 2021), endometrial cancer (Liang et al, 2021), and colorectal cancer (Huang et al, 2014;Zhou et al, 2021). Zhou et al revealed that osthole can reduce the phosphorylation of AMPK, Akt and mTOR in HCT116 and SW480 cells and induce Ferroptosis by inhibiting the AMPK/Akt/mTOR signaling pathway.…”
Section: Tcms In Combination Target Ferroptosismentioning
confidence: 99%
“…Another study in 2020 by Zhang et al first reported that Asparanin A (AA, 6–18 μM) could promote apoptosis in vitro and in vivo by activating the mitochondrial pathway and inhibiting PI3K/Akt signaling pathway ( Zhang et al, 2020 ). Recently, a study by Liang et al, in 2021 showed that Osthole (25–200 μM) could suppress the growth in vitro and in vivo , which was associated with up-regulating bax, caspase-3, -9, PARP, PETN, whereas down-regulating PI3K and Akt ( Liang et al, 2021 ).…”
Section: Effects and Mechanisms Of Nps On Apoptosis In Ecmentioning
confidence: 99%